Problematika Pembelajaran Daring di Sekolah Dasar - Aryanis, Dina Fitri; Nugroho, Oktian Fajar (JOEAI (Journal of Education and Instruction), 2023)
The purpose of this research is to find out the problems of online learning in elementary schools faced by educators, students and parents. This research uses a descriptive qualitative research type. The data source informants in the study consisted of teachers, students and three parents of class III elementary schools in one of the Legok Districts, Tangerang Regency. Data collection techniques in this study used observation, interviews and documentation. All interview data were analyzed by means of data collection, data reduction, data presentation and ending with conclusions. The results of this study state that there are problems faced by teachers, students and parents during online learning, such as low mastery of using technology, low enthusiasm of students in participating in learning, limitations in owning technological tools, difficulty in allocating time to accompany children to study at home because parents are busy working. In conclusion, online learning may be an alternative learning during the Covid 19 pandemic, but it cannot completely replace the effectiveness of face-to-face learning with all the shortcomings and obstacles experienced in online learning. Keywords: Problems, Online Learning, Elementary School